Attitudes of Australian Veterinary Professionals to Diagnosing and Managing Canine Cognitive Dysfunction - Auréa Brisset; Tracey L. Taylor; Tiphaine Blanchard; Eduardo J. Fernandez; Susan J. Hazel (Veterinary Sciences)
Canine cognitive dysfunction (CCD) is a neurodegenerative disease likely to affect 14% to 35% of dogs over the age of eight years. Although it can be associated with a high burden of care in owners of affected dogs, there is a lack of knowledge of how veterinarians diagnose and manage the disease. The aim of this study was to determine how veterinary professionals (veterinarians and veterinary nurses/technicians) manage CCD and their attitudes towards the disease using an anonymous online survey. Chi-square tests were used to assess differences according to years of experience, and multiple correspondence analysis was used to analyze clusters according to age, gender, and experience. One hundred and four responses were obtained: 73 veterinarians and 31 veterinary nurses/technicians. Veterinarians diagnosed CCD based on their own experience or by excluding other diseases (27/73, 37% and 25/73, 34%, respectively) and mostly diagnosed a few cases/year (34/73, 47%) or a few in their career (19/73, 26%). CCD was managed using specific medication or environmental changes (57/73, 78% and 58/73, 79%, respectively). Over half of veterinarians agreed/strongly agreed that they were confident in diagnosing CCD (49/73, 67%) and in giving advice on symptom management (53/73, 71%), but only 14/31 (45%) of veterinary nurses/technicians agreed that veterinarians in their practice actively treated dogs with CCD. Participants mostly agreed that CCD is associated with a large burden of care for owners, but less than half measured this burden of care. Although veterinary professionals are aware of CCD, the low rate of diagnosis suggests many dogs are undiagnosed. Increased awareness of the disease by the veterinary profession will enhance human and dog welfare.